Environmental Partitioning, Spatial Distribution, and Transport of Atmospheric Mercury (Hg) Originating from a Site of Former Chlor-Alkali Plant - Mert Guney; Aiganym Kumisbek; Zhanel Akimzhanova; Symbat Kismelyeva; Kamila Beisova; Almagul Zhakiyenova; Vassilis Inglezakis; Ferhat Karaca (Atmosphere, 2021)
Mercury (Hg) is one of the trace toxic and bioaccumulative global pollutants, and due to its long atmospheric lifetime, it presents a significant global challenge. The present study (1) utilizes total gaseous mercury (TGM) measurements made around a former Hg-cell chlor-alkali plant (CAP) located in Pavlodar, Kazakhstan, and predicts the spatial distribution of Hg over its premises and the nearby city. It then (2) estimates the environmental repartition of Hg deposited by the CAP using three fugacity models of varying complexity: Level I, QWASI, and HERMES. Finally, it (3) predicts long-range Hg transport via forward trajectory-based cluster analysis. The atmospheric Hg levels measured in Pavlodar and around Lake Balkyldak were elevated: in the range of 1–37 ng/m3 with an urban background level at 4.9 ng/m3. Specifically, concentrations up to 37 ng/m3 close to Lake Balkyldak and up to 22 ng/m3 nearby the city’s industrial zone (where the CAP was located) had been observed. Interpolation maps created using kriging also suggest these locations as the primary sources of atmospheric Hg in the city. The Level I fugacity model indicated that almost all of Hg is expected to end up in the atmosphere. The modeling results obtained using more complex QWASI and HERMES models showed that some significant quantity of Hg would still be associated with the sediments of Lake Balkyldak (a large wastewater discharge pond nearby the CAP). The forward trajectory-based cluster analysis method revealed the long-range atmospheric transportation routes and local, regional, and global impact zones. Furthermore, a source-receptor relationship using air transportation pathways to identify “areas of impact” was addressed. During both heating and non-heating seasons, the frequency-based analysis identified the distribution of Hg reaching the territories of Mongolia, northwest China, southwest Kazakhstan. The Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT-4) model forward trajectory analysis has confirmed similar patterns during heating and non-heating seasons, except with shorter impact distances during the non-heating period. Even though the CAP was closed more than 30 years ago and those past remediation efforts cleaned up the site, the residual Hg pollution seems significant and should be further investigated in different environmental media.